Insurgent Democracy: The Nonpartisan League in North American Politics - Rennie, Bradford J. (Labour / Le Travail, 2016)
The article reviews the book, "Insurgent Democracy: The Nonpartisan League in North American Politics," by Michael J. Lansing.